2008
DOI: 10.1110/ps.073307608
|View full text |Cite
|
Sign up to set email alerts
|

Design of an engineered N‐terminal HIV‐1 gp41 trimer with enhanced stability and potency

Abstract: HIV fusion is mediated by a conformational transition in which the C-terminal region (HR2) of gp41 interacts with the N-terminal region (HR1) to form a six-helix bundle. Peptides derived from the HR1 form a well-characterized, trimeric coiled-coil bundle in the presence of HR2 peptides, but there is little structural information on the isolated HR1 trimer. Using protein design, we have designed synthetic HR1 peptides that form soluble, thermostable HR1 trimers. In vitro binding of HR2 peptides to the engineere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…HR1 peptides additionally may interact with the HR1 of gp41 in a dominant negative mechanism to form a heterologous peptide-gp41 coiled coil that interferes with the endogenous coiled coil and prevents formation of the gp41 6HB (7,77,78). Since HR1 and HR2 peptides can target different sites and residues in gp41, HR1 peptides potentially represent different subclasses of fusion inhibitors with different resistance profiles.In studies aimed at understanding the mechanism of HR1 peptide inhibition and resistance, we (16) along with others (17,30) found that viruses resistant to HR1 peptide inhibitors are associated with the mutations in HR1 and HR2. Surprisingly, some of these initial reports also showed that these mutations conferred cross-resistance to HR2 peptide inhibitors (16) and, in some cases, increased in 6HB stability (16, 30).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…HR1 peptides additionally may interact with the HR1 of gp41 in a dominant negative mechanism to form a heterologous peptide-gp41 coiled coil that interferes with the endogenous coiled coil and prevents formation of the gp41 6HB (7,77,78). Since HR1 and HR2 peptides can target different sites and residues in gp41, HR1 peptides potentially represent different subclasses of fusion inhibitors with different resistance profiles.In studies aimed at understanding the mechanism of HR1 peptide inhibition and resistance, we (16) along with others (17,30) found that viruses resistant to HR1 peptide inhibitors are associated with the mutations in HR1 and HR2. Surprisingly, some of these initial reports also showed that these mutations conferred cross-resistance to HR2 peptide inhibitors (16) and, in some cases, increased in 6HB stability (16, 30).…”
mentioning
confidence: 96%
“…In studies aimed at understanding the mechanism of HR1 peptide inhibition and resistance, we (16) along with others (17,30) found that viruses resistant to HR1 peptide inhibitors are associated with the mutations in HR1 and HR2. Surprisingly, some of these initial reports also showed that these mutations conferred cross-resistance to HR2 peptide inhibitors (16) and, in some cases, increased in 6HB stability (16, 30).…”
mentioning
confidence: 96%
“…Recently, single N-HR peptides were engineered to form soluble, stable trimeric coiled-coils, and their crystal structures were similar but not identical to the trimeric core found in the 6-HB [42]. The study demonstrated that N-peptides inhibit entry by binding C-HR peptides, that the predisposition of N-peptides to form trimeric coiled-coils may be more important for anti-viral activity than the Tm of the oligomer, and that binding of C-HR to N-HR may result in conformational changes.…”
Section: Fusion Inhibitors Based On the Trimeric Coiled-coil Corementioning
confidence: 99%
“…Peptides corresponding to amino acid sequences of the gp41 carboxyl-terminal heptad repeat (C-HR) inhibit the HIV-1 fusion by acting as decoys and interfering with the formation of the six-helix bundle (Chan et al, 1998, Malashkevich et al, 1998). Although modified peptides such as SC34EK (Nishikawa et al, 2009), T-2635 (Dwyer et al, 2008), and D-peptides (Welch et al, 2007), and small molecules (Debnath et al, 1999) have been developed, T-20 (enfuvirtide) is the only fusion inhibitor approved for HIV therapy. It is a 36 amino acid peptide derived from the sequence of C-HR of gp41.…”
Section: Introductionmentioning
confidence: 99%